Pleural Fluid GSDMD Is a Novel Biomarker for the Early Differential Diagnosis of Pleural Effusion - Li, Pu; Shi, Jing; Zhou, Lijing; Wang, Bo; Zhang, Li Jun; Duan, Liang; Hu, Qin; Zhou, Xiaolan; Yuan, Yuan; Li, Dandan; Chen, Hong; Zhao, Qing; et al. (Frontiers in Microbiology, 2021)
Objective: Gasdermin D (GSDMD), controlling pyroptosis in cells, has multiple physiological functions. The diagnostic role of GSDMD in PE remains unknown. Methods: Sandwich ELISA kits that we developed were applied to measure the level of GSDMD for 335 patients with the definite cause of PE, including transudative pleural effusion, tuberculous pleural effusion (TPE), parapneumonic pleural effusion (PPE), and malignant pleural effusion (MPE). Clinical follow-up of 40 cases of PPE was conducted and divided into efficacy group and non-efficacy group according to therapeutic outcome. Nucleated cells (NCs) in pleural effusion were isolated and further infected with bacteria to verify the cell source of GSDMD. Results: The receiver operating characteristic (ROC) curve indicated that GSDMD can be an efficient biomarker for differential diagnosis of transudative pleural effusion and other groups (all AUC ＞ 0.973). Noteworthily, the highest AUC belonged to tuberculosis diagnosis of 0.990, and the cut-off value was 18.40 ng/mL. Moreover, the same cut-off value of PPE and MPE was 9.35 ng/mL. The combination of GSDMD, adenosine deaminase (ADA) and lactate dehydrogenase (LDH) will further improve the diagnostic efficiency especially between TPE and PPE (AUC = 0.968). The AUC of GSDMD change at day 4 could predict the therapeutic effect at an early stage was 0.945 (P < 0.0001). Interestingly, bacterial infection experiments further confirm that the pleural fluid GSDMD was expressed and secreted mainly by the NCs. Conclusions: GSDMD and its combination not only candidate as the potentially novel biomarkers to separate PEs early and effectively, but also monitor disease progression.